2017
DOI: 10.18632/oncotarget.19221
|View full text |Cite
|
Sign up to set email alerts
|

Application of dual targeting drug delivery system for the improvement of anti-glioma efficacy of doxorubicin

Abstract: Chemotherapy of glioma is always hampered by the unsatisfactory tumor accumulation of drugs, of which the most noticeable obstacle is the limited drug permeability from vessels into tumor inner. In the present study, we developed a novel nanocarrier for the delivery of doxorubicin to brain tumor. Such novel drug delivery system was mainly composed of a tumor homing peptide and DOX-loaded PLA nanoparticles (AP1-NP-DOX). CRKRLDRNC peptide, named as AP1, was a newly glioma affinity peptide which could specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Of the 24 articles identified in the Cochrane Library, no articles were included, as 16 articles were reviews, 5 were protocols, and 3 were clinical articles in the screening analysis. In total, only 27 full-text articles not duplicated were included in this systematic review [ 32 , 34 , 38 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 24 articles identified in the Cochrane Library, no articles were included, as 16 articles were reviews, 5 were protocols, and 3 were clinical articles in the screening analysis. In total, only 27 full-text articles not duplicated were included in this systematic review [ 32 , 34 , 38 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The major tumoral cell characteristics used in the selected studies in our review are shown in Table 1 . Of 27 selected studies for this review, 19 studies (70%) [ 32 , 34 , 38 , 43 , 45 , 48 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 62 , 63 , 64 , 65 , 66 , 67 ] used tumor cells from a human source, 6 (22%) [ 41 , 51 , 54 , 60 , 61 , 68 ] used tumor cell from rats, and 3 studies (11%) [ 44 , 50 , 66 ] used cells from mice. The study by Agemy [ 66 ] used human and mice tumor cell sources and also used lentivirus H-RasV12-shp53 to induce glioma cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations